Erythrocyte Features for Malaria Parasite Detection in Microscopic Images of Thin Blood Smear: A Review - Devi, Salam Shuleenda; Sheikh, Shah Alam; Laskar, Rabul Hussain (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Microscopic image analysis of blood smear plays a very important role in characterization of erythrocytes in screening of malaria parasites. The characteristics feature of erythrocyte changes due to malaria parasite infection. The microscopic features of the erythrocyte include morphology, intensity and texture. In this paper, the different features used to differentiate the non- infected and malaria infected erythrocyte have been reviewed.
Keywords: image processing; medicine; malaria; berythrocyte; IJIMAI